Cutaneous Leismaniasis in a Middle Aged Man - Amin, Md Robed; Islam, Shafiul; Rahman, Md Habibur; Ahmed, Farukh; Hossain, Ahmed Riyadh; Kahhar, Md Azizul (Journal of Medicine, 2012)
The incidence of cutaneous leishmaniasis (CL) is greater in the Old World than in the New World. It can be caused by several Leishmania spp and is transmitted to human beings and animals by sandflies and is usually more common in rural than urban areas, but it is found in some periurban and urban areas too. In Bangladesh there has been many cases of Post kala azar leismaniasis(PKDL) in endemic areas but pure form of cutaneous leismaniasis has not been reported many. Recently a case of cutaneous leismaniasis was diagnosed in Dhaka Medical College Hospital (DMCH) who presented with increasing number of papulonodular crusted lesions in acral parts of body. The patients although resided in Saudi Arabia, there was no history regarding risk factor to get the disease from there or in Bangladesh indicating search for exploration of disease in Bangladesh is crucial. The patient was diagnosed methodically and treated with inj Sodium Stibogluconate with complete recovery. DOI: http://dx.doi.org/10.3329/jom.v13i2.12768 J Medicine 2012; 13 : 233-236